Aterofisiol® in carotid plaque evolution - Amato B; Compagna R; Amato M; Gallelli L; de Franciscis S; Serra R (Dove Medical Press, 2015)
Bruno Amato,1,2,* Rita Compagna,1,2,* Maurizio Amato,2 Luca Gallelli,3 Stefano de Franciscis,1,4,* Raffaele Serra1–4,*1Interuniversity Center of Phlebolymphology (CIFL), International Research and Educational Program in Clinical and Experimental Biotechnology, University Magna Graecia of Catanzaro, Catanzaro, 2Department of Clinical Medicine and Surgery, University Federico II of Naples, Naples, 3Department of Health Sciences, University of Catanzaro, Catanzaro, 4Department of Medical and Surgical Sciences, University Magna Graecia of Catanzaro, Catanzaro, Italy*These authors contributed equally to this workBackground: In patients with carotid stenosis, the risk of plaque rupture is related to the composition of the atherosclerotic plaque rather than to its magnitude. In this regard, we evaluated the effects of a supplement, Aterofisiol,® containing omega-3 (EPA [eicosapen acid] DHA [docosahexaenoic acid]), vitamin K2, vitamin B6, vitamin B12, oligomeric proanthocyanidins (OPC) and resveratrol on the composition of atherosclerotic plaque and on neurological symptoms in patients with carotid stenosis undergoing carotid endarterectomy.Methods: The study was randomized, prospective, and double-blinded. Eligible patients were of both sexes, with carotid stenosis >70% who underwent endarterectomy. Enrolled patients were randomly allocated to receive either one tablet of acetylsalicylic acid 100 mg (Cardioaspirin®) + one tablet of Aterofisiol every 24 hours or one tablet of Cardioaspirin + one tablet of placebo every 24 hours. Each treatment was started 30 days before the surgery and was stopped 5 days before the surgery. The plaques were removed “en bloc” using standard surgical technique.Results: During the study period, 214 patients (135 men and 79 women) were enrolled for intent-to-treat and randomized in two groups: Group A: 107 patients (68 men and 39 women) were treated with Cardioaspirin + Aterofisiol. Group B: 107 patients (67 men and 40 women) were treated with Cardioaspirin + placebo. At the end of the study, 202 patients participated fully (103 patients in Group A and 99 patients in Group B), making up the protocol evaluation population (94.4%). The mean lipid content of removed plaques was significantly lower (P<0.05) in Group A. We recorded a significantly lower incidence of neurological symptoms in Group A in comparison with Group B (P<0.05).Conclusion: In the study, Aterofisiol showed to be effective in reducing the amounts of cholesterol and lipids in the plaques and in reducing adverse neurological events in the study group with respect to controls.Keywords: Aterofisiol®, carotid stenosis, endarterectomy, carotid plaque, neurological symptoms, cholesterol